Assessment of the impact of the great cormorant (Phalaсrocorax carbo sinensis Shaw et Nodder, 1801) on fish resources of the Obytichna Spit the Sea of Azov - A. Sydorenko (Ribogospodarsʹka Nauka Ukraïni)
Purpose. Assessment of the impact of the great cormorant (Phalacrocorax carbo) on fish resources of the Sea of Azov and determination of dietary needs and feeding habits of this species during its nesting period on the Obytichna Spit (Zaporizhzhia region).